2015
DOI: 10.1118/1.4928674
|View full text |Cite
|
Sign up to set email alerts
|

Permanent‐magnet energy spectrometer for electron beams from radiotherapy accelerators

Abstract: The apparatus and analysis techniques of the authors demonstrated that an inexpensive, lightweight, permanent magnet electron energy spectrometer can be used for measuring the electron energy distributions of therapeutic electron beams (6-20 MeV). The primary goal of future work is to develop a real-time spectrometer by incorporating a real-time imager, which has potential applications such as beam matching, ongoing beam tune maintenance, and measuring spectra for input into Monte Carlo beam calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Based on the results of the present study, we conclude that a lightweight, permanent magnet spectrometer1 is a useful tool for measuring energy spectra of matched therapeutic electron beams, allowing their comparison and evaluation, both qualitatively and quantitatively. Comparison of energy spectra for all beams on a single accelerator in most cases showed that the PME and FWHM of the energy spectra did not always smoothly vary monotonically with beam energy, as otherwise expected.…”
Section: Summary and Recommendationsmentioning
confidence: 55%
See 3 more Smart Citations
“…Based on the results of the present study, we conclude that a lightweight, permanent magnet spectrometer1 is a useful tool for measuring energy spectra of matched therapeutic electron beams, allowing their comparison and evaluation, both qualitatively and quantitatively. Comparison of energy spectra for all beams on a single accelerator in most cases showed that the PME and FWHM of the energy spectra did not always smoothly vary monotonically with beam energy, as otherwise expected.…”
Section: Summary and Recommendationsmentioning
confidence: 55%
“…For each machine, energy spectra were measured for all energies on a single day using the permanent magnet spectrometer previously fabricated by Rice University (Houston, TX) and described by McLaughlin et al 1. The energy spectra were measured for that portion of the electron beams on central‐axis at 95‐cm SCD, which passes through a 0.278‐cm diameter aperture in a 1.59‐cm thick Cerrobend collimating insert placed in the 14 × 14 cm 2 applicator (cf Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a considerable interest in the magnetic systems on the base of rare-earth permanent magnets for use in special accelerators such as medical and technological accelerators, microtrons, liner colliders and etc [1][2][3][4][5]. The creation of each such device is associated with the need to take into account the parameters of accelerators and the features of their operation.…”
Section: Introductionmentioning
confidence: 99%